1992
DOI: 10.1080/01952307.1992.11735862
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Spinal Cord Injured Males: Effect of Genitourinary Infection and Bladder Management on Results of Electroejaculation

Abstract: Thirty-eight men undergoing electroejaculation (EEJ) procedures for anejaculatory infertility were examined for the presence or absence of infection in urine and semen. In 29 spinal cord injury patients, a high incidence of infected urine and infected semen (41% and 56%, respectively) was seen, in contrast to patients with normal bladder function (0% and 11%). Urinary infection was associated with slightly lower sperm quality and lower pregnancy rates (10% vs 30% in the presence of sterile urine). Semen infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 15 publications
2
31
0
3
Order By: Relevance
“…53 The method of bladder management used has also been shown to a ect semen quality. 54 In a previous study by this clinic, both method of bladder management and neurological level proved to be signi®cant factors a ecting the presence of motile sperm. Low pressure bladder emptying by catheter drainage (either permanent indwelling catheter or intermittent self catheterisation) resulted in a higher percentage of motile sperm compared to individuals using re¯ex voiding or straining.…”
Section: Discussionmentioning
confidence: 84%
“…53 The method of bladder management used has also been shown to a ect semen quality. 54 In a previous study by this clinic, both method of bladder management and neurological level proved to be signi®cant factors a ecting the presence of motile sperm. Low pressure bladder emptying by catheter drainage (either permanent indwelling catheter or intermittent self catheterisation) resulted in a higher percentage of motile sperm compared to individuals using re¯ex voiding or straining.…”
Section: Discussionmentioning
confidence: 84%
“…The mean age of the female partners was 34.5 ± 4.66 years (range 26-44). The mean age at injury of the male partners was 21.7±4.3 years and the average interval till the ART procedure was carried out was 7.6±2.1 years (range [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on various methods of bladder management have confirmed that intermittent achieved a higher percentage of motile sperms as compared to high pressure voiding by reflex or straining. 5,6 Ohl et al 5 have also concluded that urinary infection is associated with slightly lowersperm quality and lower-pregnancy rates as compared to presence of sterile urine, 10 versus 30%. Decline in semen quality appears to begin within the first few weeks of injury, but the exact point in time when deterioration starts has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%